Understanding tablet computer usage among primary school students in underdeveloped areas: Students' technology experience, learning styles and attitudes. (February 2016) - Pruet, Putjorn; Ang, Chee Siang; Farzin, Deravi
Abstract: The need to provide low-cost learning technologies such as laptops or tablet computers in developing countries with the aim to bridge the digital divide as well as addressing the uneven standards of education quality has been widely recognised by previous studies. With this aim in mind, the Thai Government has launched the "One Tablet PC Per Child" (OTPC) policy and distributed 800, 000 tablet computers to grade-one students nationwide in 2012. However, there is limited empirical evidence on the effectiveness of tablet computer use in the classroom. Our study examined students' learning styles, attitudes towards tablet computer use and how these are linked to their academic performance. The study has investigated 213 grade two students in economically underprivileged regions of North Thailand. Data collection was based on questionnaires filled in by the students with the help of their teachers. Our results overall suggested that there were some key significant differences in relation to students' gender and home locations (urban vs. rural). In contrast to existing studies, both genders at this stage had similar technology experience and positive attitudes towards tablet computer use. However, we found girls had higher visual learning style ( M = 4.23, p < .032) than boys ( M = 3.96). Where home location was concerned, rural students had higher learning competitiveness and higher levels of anxiety towards tablet use ( M = 1.71, p < .028) than urban students ( M = 1.33). Additionally, we also found technology experiences, collaborative learning style and anxiety affected students' academic performance.